Rowan Williams' Theology of Revelation - Vines, Lachlan (Journal of Anglican studies, 2025)
In this essay, I explore two main areas of Rowan Williams' theology of revelation. The former is his reflections on the silence of God - God's reticence to clarify himself to us amid our theological and spiritual confusion. I argue that he is not denying that God has genuinely revealed himself to us, but rather Williams is grappling with - and exhorting us to grapple with - the limits of that revelation. The second area I explore is his theory of revelation as generative phenomena, and how his theory underwrites his understanding of church tradition and, mainly, scripture. Williams argues that there is a division within scripture between the parts containing true divine revelation and the parts containing humanity's broken response to that revelation. I argue that this view, while it is very well formulated and has some merits, cannot surmount the epistemological obstacle of how biased and interested humans can adequately differentiate between these parts within scripture.